Et fut lancé le Groupe Dupont (1971-2016)… - Annick Douguédroit (Bulletin de l’Association de Géographes Français)
The « Groupe Dupont » created in Avignon in 1971 was one component of the French geographical revival during the 1970 decade. Launched by J.-P. Ferrier and H. Chamussy, and formed by university geographers of greater southeastern France, its purpose was, at its beginning, to train for quantitative geography, already developped by the Anglo-American geography, to use it in their research. Its participants, all of them coming from universities but preoccupied to keep themselves far from all mandarinal influence, kept the group without attachment to any institution, academic or not.